2002
DOI: 10.1023/a:1014590000158
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In this paper we show how, under certain restrictions, the hydrodynamic equations for the freely evolving granular fluid fit within the framework of the time dependent Landau-Ginzburg (LG) models for critical and unstable fluids (e.g. spinodal decomposition). The granular fluid, which is usually modeled as a fluid of inelastic hard spheres (IHS), exhibits two instabilities: the spontaneous formation of vortices and of high density clusters. We suppress the clustering instability by imposing constraints on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…(7), and the homogeneous granular temperature, Eq. (20), where the dimensionless critical shear rate for the neutral stability is found to be…”
Section: Linear Stability Analysismentioning
confidence: 99%
“…(7), and the homogeneous granular temperature, Eq. (20), where the dimensionless critical shear rate for the neutral stability is found to be…”
Section: Linear Stability Analysismentioning
confidence: 99%
“…Wakou et al [12] have shown that fluctuations in these quantities obey TDGL-like equations of phase ordering dynamics with a nonconserved order parameter [10]. Typically, these equations are obtained as the overdamped limit of a Hamiltonian formulation.…”
mentioning
confidence: 99%
“…The existence of this free shear state has been suggested previously in the framework of a time-dependent Ginzburg-Landau model for granular gases [10], and also as the result of a nonlinear analysis of the shearing instability [16]. The theory presented in this paper differs from those studies both in the method and the results, where rather strong discrepancies occur as it will be discussed along the paper.…”
Section: Introductionmentioning
confidence: 70%
“…The latter happens to be smaller than the critical size for the instability of one of the longitudinal modes associated with the density [9,10]. Consequently, the spatial inhomogeneities of the hydrodynamic fields are expected to be small.…”
Section: Introductionmentioning
confidence: 95%